Exploring Marine Invertebrate-Associated Bacteria for Novel Antibiotics: Isolation, Activity Screening, and Potential Bioactive Compounds - Wibowo, Joko Tri; Rachman, Fauzy; Untari, Febriana; Zedta, Raymon Rahmanov; Utama, Rizkie Satriya; Handayani, Ira; Setiawan, Ruby; Hertiani, Triana (Indonesian Journal of Pharmacy, 2025)
Marine bacteria associated with marine invertebrates are an interesting source to find compounds with potential bioactivities due to their ability to survive along with their host through evolution. Recent studies also found that secondary metabolites that previously isolated from marine invertebrates such as bryostatins were produced by the bacterial symbionts. Therefore, we screened bacteria from various marine invertebrates in Pulau Pari, Kepulauan Seribu, Jakarta for their antibacterial activities. The aim of this study to obtain potential bacterial strains that produce novel antibiotics. Isolation of bacteria from 16 marine invertebrates were accomplished using media Marine Agar, ISP2, YMA, and MS. We picked 97 bacterial strains for the testing of antibacterial activity against Mycobacterium smegmatis, Staphylococcus aureus, Eschericia coli, Pseudomonas aeruginosa, and Bacillus subtilis. The result showed that 19 of the bacterial strains showed activity against at least one of the test bacteria. One of the strains exhibited potent antibacterial activity against M. smegmatis. Partial identification using 16S rRNA revealed that the strains has 99.58% sequence similarity to Micrococcus luteus NCTC 2665T. Chemical analysis using GC-MS showed 9,12- Octadecadienoic acid, methyl ester; 9,12-Octadecadienoic acid (Z,Z); Octadecanoic acid; 2-(Dimethylamino)ethyl vaccenoate; and Cyclopropane,1,1-dichloro-2,2,3,3-tetramethyl- were major compounds with putative antibacterial activity. The results of this study emphasize the prospect of targeting this strain for further exploration to isolate and to characterize novel antibiotics from marine bacteria.